THE ROLE OF A MEDICAL DOCTOR AS A HEALTH LAW SPECIALIST AS AN EXPERT WITNESS IN THE JUSTICE SYSTEM IN INDONESIA - Erald Giovanny Hasiholan Simatupang; Hadi Purnomo (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
The science of criminal law provides requirements to say that a person committing a crime must fulfill the elements of an act that legally violates the law or has a normative nature against the law. Provide expert testimony in a criminal case. The presence of a doctor who is an expert in health law as an expert witness can be requested by the prosecutor or the suspect's legal adviser with the approval of the judge. This paper aims to find out the role and position of a medical law expert as an expert witness in the criminal justice system. The research method in this paper uses a literature review by applying a qualitative research approach. The results of the discussion show that the role of doctors who are experts in health law as legal agents for law enforcement officials and in the criminal justice system is positioned as an expert in every stage of court proceedings. From the research, it was concluded that doctors who are experts in health law play a vital role in assisting law enforcement officials in proving criminal cases that have occurred as expert witnesses in court. As a suggestion, it is necessary to have strict rules governing the position of doctors who are experts in health law as expert witnesses. In addition, there is a need for coordination between law enforcement officials and doctors to make clear the crimes that have occurred.